SWCC of Calcareous Silty Sand Under Different Fines Contents and dry Densities - Shen, Jian-Hua; Hu, Ming-Jian; Wang, Xing; Zhang, Chen-Yang; Xu, Dong-Sheng (Frontiers in Environmental Science, 2021)
Investigating the soil-water characteristics of calcareous soil has great significance for assessing vegetation ecological processes on island-reefs. In this study, calcareous silty sands with different fines contents and dry densities were studied to reveal the effects of fines content and dry density on the soil-water characteristics of calcareous soil on hydraulic-filled island-reefs. The soil-water characteristic curve (SWCC) of the calcareous silty sand was measured using a pressure plate apparatus. Taking into account the porous meso-structure, the effects of fines content and dry density on the SWCC of calcareous silty sand were analyzed, and the applicability of existing SWCC models to calcareous silty sand was verified. A SWCC model suitable for assessing soil-water characteristic of calcareous silty sand was proposed. Results of this study can provide some references for quantifying the water-holding capacity of calcareous silty sand.